A risk-benefit approach to the purchase and consumption of conventional vegetables in wet markets. (1st September 2022) - Ha, Thanh Mai; Hansson, Helena; Abu Hatab, Assem; Darr, Dietrich; Shakur, Shamim
Abstract: The purchase and consumption of conventional vegetables from wet markets in Vietnam are like two sides of a coin: perceived food safety risks and perceived benefits. Drawing on a sample of 463 Hanoi consumers, this study employed a risk-benefit approach to analyze the purchase intention and consumption frequency of conventional vegetables at traditional markets. A confirmatory factor analysis examined the links among risk perception, perceived utilitarian benefits, perceived hedonic benefits, and trust. Finally, generalized ordered and Poisson regressions were performed on these psychological constructs and their identified links. We found that perceived hedonic benefits, trust in wet market actors, and the presence of homegrown vegetables determined purchase intention and consumption frequency. The joint influence of perceived hedonic and utilitarian benefits on purchase intention implies that consumers considered both benefit dimensions when thinking of their future purchase of conventional vegetables. The significant interaction between perceived risk and perceived hedonic benefits on consumption frequency supports the risk-benefit approach. The effect of perceived hedonic benefits and income on purchase intention and consumption frequency are evidence of wet markets' social and cultural relevance. Highlights: Shopping conventional vegetables at wet markets is common in Vietnam despite food safety concerns. Utilitarian and hedonic benefit jointly influence the buying intention of conventional vegetables. Utilitarian benefits are a more important driver of purchase intention than hedonic benefits. Perceived risks and perceived benefits exert a joint effect on consumption frequency. Social and cultural values offered by wet markets explain their stable existence in Vietnam.